Evaluation of the understanding of antibiotic resistance among Malaysian pharmacy students at public universities: an exploratory study - Rajiah, Kingston; Wong, S.Ren; Jamshed, Shazia Qasim (Elsevier, 2015)
Background Infectious diseases are a great threat to humankind, and antibiotics are a viable proposition to numerous pathologies. However, antibiotic resistance is a global concern. Therefore, the aims of this survey were to explore the understanding and attitudes of pharmacy students regarding antibiotic use and resistance.